Compression and shearing force on kernel rupture in shelling fresh lotus seeds - He, Jincheng; Tao, Zhiying; Liang, Shihua; Ye, Dapeng (International Journal of Agricultural and Biological Engineering, 2021)
The mechanical properties of fresh lotus seeds are still poorly understood, which complicates the design of mechanical shelling machinery. Therefore, this work carried out four-factor orthogonal tests to determine the maximum permitted compressive force and minimum necessary shearing force to shell fresh lotus seeds without rupturing the kernel. It was found that the mean compression force that cracked the fresh lotus seed and led to kernel rupture was 213.03 N. Both the compressive force and the seed deformation upon kernel rupture were affected, in descending order of significance, by loading mode, seed grade, loading rate, and seed standing time. On the other hand, the shearing force needed to shell the seeds had a mean value of 7.84 N, far less than the compressive force that cracked the seed shell. The shearing force was affected, in descending order of significance, by seed standing time, tip angle of cutter blade, and loading rate, but not significantly affected by seed grade. The results suggested that mechanical shelling of fresh lotus seeds should ideally be carried out for fresh lotus seeds with a standing time of no more than 6 h using a cutter blade with an angle of about 40° at a loading rate of 30-90 mm/min. Keywords: shelling fresh lotus seeds, mechanical properties, shearing, compression, kernel rupture DOI: 10.25165/j.ijabe.20211401.5193 Citation: He J C, Tao Z Y, Liang S H, Ye D P. Compression and shearing force on kernel rupture in shelling fresh lotus seeds. Int J Agric & Biol Eng, 2021; 14(1): 237–242.